Efficacy and Selectivity of Different Herbicides on the Transplanted Late Boro Rice under the Lateritic Soil of West Bengal - Gupta, Rahul Kumar; Ghosh, Pritam; Aparna, Mahanti; Bharti, Ruchi; Pramanik, Kalipada (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during the late boro seasons (January–May) of 2018 and 2019 to assess the impact of herbicides on rice growth, yield and weed control in transplanted rice in the Agricultural Farm of Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati University, Sriniketan, West Bengal, India. There were eight different treatments consisting of pretilachlor 50 EC @ 500 g ha-1 at 3 DAT, pyrazosulfuron ethyl 10 WP @ 30 g ha-1 at 3 DAT, ethoxysulfuron 15 WDG @ 15 g ha-1 at 10 DAT, penoxsulam 21.7 SC @ 22.5 g ha-1 at 12 DAT, bispyribac-sodium 10 SC @ 25 g ha-1 at 15 DAT, hand weeding at 20 and 40 DAT, weed-free check and weedy check. Results from the pooled analysis of both the years revealed that pyrazosulfuron ethyl 30 g ha-1 and pretilachlor at 500 g ha-1 resulted in lower weed population and dry weight; higher plant height, number of tillers m-2, dry matter accumulation, leaf area index; grain and straw yield (5.98 and 7.81 t ha-1 and 5.81 and 7.62 t ha-1 respectively). The lowest weed index was registered by pyrazosulfuron ethyl 30 g ha-1 and pretilachlor at 500 g ha-1 and was superior to all other herbicidal treatments. Yield loss due to weeds infestation throughout the crop season was to the extent of 54.33%. Thus, pyrazosulfuron ethyl 30 g ha-1 and pretilachlor at 500 g ha-1 as pre-emergence may be recommended for effective weed control in transplanted late boro rice.